A comparison of arterial spin labeling perfusion MRI and DCE‐MRI in human prostate cancer. (9th May 2014) - Cai, Wenchao; Li, Feiyu; Wang, Jing; Du, Huarui; Wang, Xiaoying; Zhang, Jue; Fang, Jing; Jiang, Xuexiang
<x xml:space="preserve">Abstract</x> Perfusion MRI has the potential to provide pathophysiological biomarkers for the evaluating, staging and therapy monitoring of prostate cancer. The objective of this study was to explore the feasibility of noninvasive arterial spin labeling (ASL) to detect prostate cancer in the peripheral zone and to investigate the correlation between the blood flow (BF) measured by ASL and the pharmacokinetic parameters Ktrans (forward volume transfer constant), kep (reverse reflux rate constant between extracellular space and plasma) and ve (the fractional volume of extracellular space per unit volume of tissue) measured by dynamic contrast‐enhanced (DCE) MRI in patients with prostate cancer. Forty‐three consecutive patients (ages ranging from 49 to 86 years, with a median age of 74 years) with pathologically confirmed prostate cancer were recruited. An ASL scan with four different inversion times (TI = 1000, 1200, 1400 and 1600 ms) and a DCE‐MRI scan were performed on a clinical 3.0 T GE scanner. BF, Ktrans, kep and ve maps were calculated. In order to determine whether the BF values in the cancerous area were statistically different from those in the noncancerous area, an independent t‐test was performed. Spearman's bivariate correlation was used to assess the relationship between BF and the pharmacokinetic parameters Ktrans, kep and ve. The mean BF values in the cancerous areas (97.1 ± 30.7, 114.7 ± 28.7, 102.3 ± 22.5, 91.2 ± 24.2 ml/100 g/min, respectively, for TI = 1000, 1200, 1400, 1600 ms) were significantly higher (p < 0.01 for all cases) than those in the noncancerous regions (35.8 ± 12.5, 42.2 ± 13.7, 53.5 ± 19.1, 48.5 ± 13.5 ml/100 g/min, respectively). Significant positive correlations (p < 0.01 for all cases) between BF and the pharmacokinetic parameters Ktrans, kep and ve were also observed for all four TI values (r = 0.671, 0.407, 0.666 for TI = 1000 ms; 0.713, 0.424, 0.698 for TI = 1200 ms; 0.604, 0.402, 0.595 for TI = 1400 ms; 0.605, 0.422, 0.548 for TI = 1600 ms). It can be seen that the quantitative ASL measurements show significant differences between cancerous and benign tissues, and exhibit strong to moderate correlations with the parameters obtained using DCE‐MRI. These results show the promise of ASL as a noninvasive alternative to DCE‐MRI. Copyright © 2014 John Wiley & Sons, Ltd.